OPTIMALISASI STRUKTUR DAN REGULASI LEMBAGA KEUANGAN SYARIAH DI INDONESIA (IAIN Tulungagung, 2020)
Islamic Financial Institutions have a very important position as a sharia-based Islamic economic institution in the middle of the national development process. The establishment of Islamic financial institutions is an implementation of the understanding of Muslims towards muamalah principles in Islamic economic law which are then presented in the form of Islamic economic institutions such as bank and non-bank Islamic financial institutions. Islamic financial institutions are important instruments in Islamic economic development, where the public or the state cannot ignore the importance of establishing its institutions. Since 1991, the existence of an Indonesian sharia financial institution is a kind of Islamic bank (BMI and BPRS) as an alternative banking institution that is free from money development practices. Similar practices are followed by sharia non-bank Islamic financial institutions such as Insurance, Islamic Capital Market, Pawn, Leassing, BMT, Financing, Hiwalah, and others.